Patient Screenings for Preconception Health Interventions at a Community Pharmacy - Alex J Luli; Natalie Tran; Angela Ataya; Sally Rafie (MDPI AG, 2020)
Preconception health refers to health before pregnancy and involves addressing risk factors that can negatively impact either a patient or future pregnancy. Pharmacists can play an essential role in screening for and managing patients' risk factors to optimize pregnancy outcomes. The primary objective of this study is to determine whether preconception health screenings in community pharmacy settings identify opportunities for preconception health services, particularly pharmacy-based interventions. The secondary objectives are to describe the preconception health status of community pharmacy patients and their interest in receiving preconception care services by a clinical pharmacist in a community pharmacy setting. Two independent pharmacies conducted a pilot project where people were invited to complete a health screening form that evaluated their preconception health. Participants received a personalized health report with an invitation to meet with the clinical pharmacist for services related to identified opportunities, such as contraception and immunizations. Retrospective analysis was conducted for data collected from 43 women during the patient screening effort in three community pharmacy settings (two independent community pharmacy locations and one neighborhood pharmacy outreach event). Nearly all participants (n = 42, 98%) had at least one opportunity identified to receive preconception care services, with the majority related to their alcohol use (60%). A majority of participants (56%) indicated an interest in learning more about preconception services offered at the pharmacy, but only 19% wanted to schedule an appointment with a pharmacist. Thus, there is an apparent need and opportunity for utilization of preconception health services at the pharmacy.